Sistem Informasi Penerimaan Kas Tunai SPP Pada RA Rima Alamanda Bekasi Menggunakan Php Dan MySQL - Tiara Pingkan Sugara (ALMUISY: Journal of Al Muslim Information System, 2023)
Rima Alamanda Kindergarten Bekasi is one of the Kindergarten schools in the Perum Pesona Gading Cibitung Blok H1/23 area of Bekasi districts. In carrying out its activities, the current system in managing administration, especially tuition payments, recording and managing school payment data, still uses simple data management, namely Microsoft Office Excel and has not been integrated. This causes frequent problems such as data inaccuracies, especially the lack of student tuition fees, errors in recording data and information regarding the remaining amount of tuition payments and difficulties in finding data because it takes a long time when parents ask for student tuition deficiencies. The process of recapitulating student SPP data which still has to be recapitulated manually, so it takes a long time to present the SPP income report if requested by the Principal. This study designs a system that can make the process of paying student tuition fees effectively and efficiently using PHP and MySQL. With the development of this information system, the transaction process for student tuition payments has been based on an information system with data storage to a database, thus eliminating paper and MS records. Excel. With this system it also makes it easier to see the lack of student tuition payments with accurate data and makes it easier to find information on lack of payment and makes it easier to recap student tuition payment reports without having to manually recap again. Keyword: Cash SPP, Financial Administration, Transactions, Reports, PHP, MySQL.